2018
DOI: 10.1101/488015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Focus on the spectra that matter by clustering of quantification data in shotgun proteomics

Abstract: In shotgun proteomics, the information extractable from label-free quantification experiments is typically limited by the identification rate and the noise level in the quantitative data. This generally causes a low sensitivity in differential expression analysis on protein level. Here, we propose a quantification-first approach for peptides that reverses the classical identification-first workflow. This prevents valuable information from being discarded prematurely in the identification stage and allows us to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…To specifically identify candidate antineural autoantibodies in the CSF, we searched for mouse proteins that were observed in both technical replicates and significantly enriched by spectral counting and/or 1.53 enriched by MS1 peak area in COVID-19 CSF IP relative to controls. 32 Between 5 and 56 (median = 20) proteins were enriched by the CSF, but not by the plasma, of the same case or control CSF, indicating that they were unique to the CSF compartment of individuals with COVID-19. Gene Ontology pathway analysis indicated that COVID-19 CSF and plasma IP-MS fractions were enriched for brain-enriched and synaptic proteins.…”
Section: Ip-ms Identifies Intrathecal Candidate Autoantigens In a Subset Of Individuals With Covid-19mentioning
confidence: 90%
See 1 more Smart Citation
“…To specifically identify candidate antineural autoantibodies in the CSF, we searched for mouse proteins that were observed in both technical replicates and significantly enriched by spectral counting and/or 1.53 enriched by MS1 peak area in COVID-19 CSF IP relative to controls. 32 Between 5 and 56 (median = 20) proteins were enriched by the CSF, but not by the plasma, of the same case or control CSF, indicating that they were unique to the CSF compartment of individuals with COVID-19. Gene Ontology pathway analysis indicated that COVID-19 CSF and plasma IP-MS fractions were enriched for brain-enriched and synaptic proteins.…”
Section: Ip-ms Identifies Intrathecal Candidate Autoantigens In a Subset Of Individuals With Covid-19mentioning
confidence: 90%
“…The Quandenser pipeline consists of Quandenser, Crux, and Triqler. 32 PhIP-Seq Bioinformatic Analysis Raw FASTQ reads generated from the PhIP-Seq peptidome assay were aligned to our reference PhIP-Seq database using RAP-Search (v2.2). Peptide counts outputted from this workflow were normalized to reads per 100 thousand (RPK) for every sample by dividing each peptide count by the sum and multiplying by 100,000.…”
Section: Quandenser (Ms1 Peak Area)mentioning
confidence: 99%
“…To estimate the rate at which false transfers occur, we adopted a supervised semiparametric mixture model that we previously applied in a number of related applications (19,20). For each successfully transferred donor ion (i.e., target ion), we try to transfer a decoy ion, created to have the same retention time and ion mobility (if applicable) but with a large m/z shift (31)(32)(33). To generate a decoy, we first shift the m/z by +11 × 1.0005 Th.…”
Section: Mbr False Discovery Rate Estimationmentioning
confidence: 99%
“…To estimate the rate at which false transfers occur, we adopted a supervised semi-parametric mixture model that we previously applied in a number of related applications (19, 20). For each successfully transferred donor ion (i.e., target ion), we try to transfer a decoy ion, created to have the same retention time and ion mobility (if applicable) but with a large m/z shift (28, 29). To generate a decoy, we first shift the m/z by +11×1.0005 Th.…”
Section: Introductionmentioning
confidence: 99%